A project feasibility on Solar Dryer Company makers of Sunshine Dryers - Del Rosario, Francis Edward N.; Gonzales, Jonas R.; Po, Ronald Aaron U. (Diliman, Quezon City College of Engineering, 2002)
Solar Dryer Company is an organization that will forego the production and promotion of non-grain solar dryers in the Philippines. It is with this undertaking that the company hopes to improve the agricultural situation in the country through technology capable of increasing post-harvest processes such as drying. In addition, the utilization of renewable energy (solar) in the product promotes environment friendly methods in slowly revolutionizing the world's approach on using non-fossil fuel dependent machineries and equipment. With these objectives, the company determined the feasibility of the Sunshine Dryer in the market. It was determined that for a new technology, the Sunshine Dryer has a relatively healthy market share for the first five years and in fact has the opportunity to garner 80% of the market by the end of the fifth year. There exist only two types of competitors: the mechanical dryer and the traditional sun-dried method of which the Sunshine Dryer outnumbers in advantages and opportunities. The target market includes cooperatives, small companies and farmers who are ready to invest in such a product for increased returns and for the production of better quality goods. To tap the market, the company plans to go through the different media available appropriate for such an industry. Considering all the areas to ensure that the company will get the desired market share, the marketing budget comes to a total of Php 266,000.00. After conducting the market study and obtaining the product specifications, the technical study was undergone. Through the technical study, it was determined that there exists a more than ample supply of raw materials and raw materials suppliers as well as machineries and equipment and their suppliers needed for the production of Sunshine Dryer. This was done after determining the processes the product will undergo to complete production and assembly. Capacity planning was also undertaken and the company identified the number of laborers needed to meet the market demand projected in the initial study. The assembly will be a "pull" system and the production plan was set. The company opted to go for a partnership type of an organization. Given all the information, the investment cost projected is Php 2,808,287.71. Financial projections were made by using different financial statements. Pro-forma income statements result in small net losses in the first and fifth year of operation while substantial net incomes were realized in the other year. Projected cash flow statements show that the company's cash balance increased up to 5,336,351.21 Php at the end of the fifth year of operation. Financial analyses yielded positive figures which prove the company's profitable operation. The project generates an internal rate of return (IRR) of 92% with a net present value (NPV) of 1,005,120.89 Php. Social profitability analyses yielded profitable figures for the company's contribution to government and society (through employment). Most notable of these contributions are the company's contribution to the environment and the development of indigenous industries.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management.
Keywords: Solar dryers; Food -- Solar drying -- Equipment and supplies; Participatory monitoring and evaluation (Project management)